2002
DOI: 10.1097/00005768-200209000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Possible mechanism of quadriceps femoris weakness in patients with ruptured anterior cruciate ligament

Abstract: Our results suggest that loss of feedback from mechanoreceptors in ACL is the underlying mechanism of weakness of QF in patients with ACL lesion. This conclusion is based on chronic suppression of recruitment of high-threshold motor units during voluntary contraction because ACL lesion leads to chronic reduction in Ia-feedback to muscles around the knee due to a lack of feedback from ACL to gamma motor neurons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
130
1
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(142 citation statements)
references
References 14 publications
7
130
1
4
Order By: Relevance
“…In this situation a reciprocal inhibition of this muscle occurs in order to avoid the increase of the tibia shearing in relation to the femur (8)(9) . Moreover, this quadriceps inhibition may be caused by the loss of mechanoreceptors placed in the ACL (8)(9)11) or type II fibers atrophy (23) . According to these results one may suggests that the Fmed may be a parameter for the characterization of the ACL lesion, confirming the results by McNair et al (23) who found significant decrease of the Fmed in the limbs with ACL lesion when analyzing the Fmed behavior in the VL muscle in individual with ACL lesion, comparing injured limb with contralateral healthy limb.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this situation a reciprocal inhibition of this muscle occurs in order to avoid the increase of the tibia shearing in relation to the femur (8)(9) . Moreover, this quadriceps inhibition may be caused by the loss of mechanoreceptors placed in the ACL (8)(9)11) or type II fibers atrophy (23) . According to these results one may suggests that the Fmed may be a parameter for the characterization of the ACL lesion, confirming the results by McNair et al (23) who found significant decrease of the Fmed in the limbs with ACL lesion when analyzing the Fmed behavior in the VL muscle in individual with ACL lesion, comparing injured limb with contralateral healthy limb.…”
Section: Discussionmentioning
confidence: 99%
“…When the ACL is injured, the lesion affects not only the joint stability but also the neuromuscular performance, with consequent weakness of the TQ muscle due to the loss of the mechanoreceptors placed there. This lack of receptors suppresses the recruiting of the motor units during voluntary contraction and such blocking of the sensory inference results in the inactivation of the periarticular muscles (8)(9)11) . Williams et al (9) , observed through surface electromyography (SEMG), decrease in the voluntary muscle activation of the TQ muscle in individuals with ACL lesion compared with individuals without lesion during static and dynamic exercises.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in gait pattern may occur as a consequence of joint tissue derangement, knee joint swelling, weakness of the quadriceps femoris muscle or muscle inhibition due to pain 6 . Atrophy of the extensor muscles is a common finding among patients undergoing anterior cruciate ligament (ACL) reconstruction [7][8][9] . Therefore, recovery of knee extensor strength is essential for functional rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that training using eccentric contractions is more effective for muscle recovery because it promotes greater changes in neural activation and muscle hypertrophy [9][10][11][12] . Both force generation and stretching are major factors in activating protein synthesis, and the combination of these stimuli apparently has a pronounced additive effect 13 .…”
Section: Introductionmentioning
confidence: 99%
“…5,6 The PCL is not just a collagen tissue for structural support but has neural elements (monoreceptors) that aid integration into the musculoskeletal system 6,7 and provide proprioception to the body by mediating knee kinesthesia and statics leading to dynamic stability. [8][9][10] Although decrease in monoreceptors and mucoid degeneration of collagen fibres occurs with the onset of osteoarthrosis, 11,12 PCL-retaining knees are reported to achieve better proprioception. 13,14 However, PCL-sacrificing knees are also reported to achieve similar proprioception.…”
mentioning
confidence: 99%